New developments in surgery of malignant gliomas - Vranič, Andrej (Radiology and oncology (Ljubljana), 2011)
Background. Malignant gliomas account for a high proportion of brain tumours. With new advances in neurooncology, the recurrence-free survival of patients with malignant gliomas has been substantially prolonged. It, however, remains dependent on the thoroughness of the surgical resection. The maximal tumour resection without additional postoperative deficit is the goal of surgery on patients with malignant gliomas. In order to minimize postoperative deficit, several pre- and intraoperative techniques have been developed. Conclusions. Several techniques used in malignant glioma surgery have been developed, including microsurgery, neuroendoscopy, stereotactic biopsy and brachytherapy.Imaging and functional techniques allowing for safer tumour resection have a special value. Imaging techniques allow for better preoperative visualization and choice of the approach, while functional techniques help us locate eloquent regions of the brain.
Keywords: gliom; kirurško zdravljenje; radiologija; rak (medicina); slikovna diagnostika